2014
DOI: 10.1094/pdis-01-14-0093-re
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Economics of Integrating In-Field and Harvesting Strategies to Manage Fusarium Head Blight of Wheat

Abstract: A b s tra c t Salgado, J. D., Madden, L. V., and Paul, P. A. 2014. Efficacy and economics of integrating in-field and harvesting strategies to manage Fusarium head blight of wheat. Plant Dis. 98:1407-1421.Fusarium head blight (FHB), a fungal disease of wheat caused by Fusarium graminearum, and its associated toxins, particularly deoxynivalenol (DON), are best managed by integrating multiple strategies. Experiments were established in 2011 and 2013 to evaluate the effects of integrating cultivar resistance, fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 44 publications
1
26
0
Order By: Relevance
“…Consequently, grain contaminated with DON above 2 ppm (threshold established by the United States Food and Drug Administration) may be rejected or priced down by grain buyers (25,26). Further price discounts are usually applied to grain lots with Fusarium-damaged kernels (FDK) above and test weight below established thresholds (26,40,41).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, grain contaminated with DON above 2 ppm (threshold established by the United States Food and Drug Administration) may be rejected or priced down by grain buyers (25,26). Further price discounts are usually applied to grain lots with Fusarium-damaged kernels (FDK) above and test weight below established thresholds (26,40,41).…”
mentioning
confidence: 99%
“…Many of the moderately resistant soft red winter wheat cultivars have low-to-moderate yield potential when compared with some of the susceptible cultivars. Consequently, producers may earn less as a result of lower grain yield if a resistant cultivar is planted in a low-disease year (40). Similarly, because fungicides are not 100% effective against FHB (11,33,49), producers may incur the costs associated with spraying their fields without seeing the benefits in terms of disease and toxin reduction and grain yield and quality increase.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yoshida et al (2012) demonstrated that DON could be reduced by applying the fungicide thiophanate-methyl at 20 DAA, but this application timing would not be practical in winter wheat due to the relatively short period of time between anthesis and harvest (~30e40 days). Several studies have evaluated the effect of moderately resistant cultivars on DON levels, but no cultivars have yet been developed that are completely resistant to DON accumulation (Bai et al, 2001;Saldago et al, 2014). Therefore, although combinations of moderately resistant cultivars and fungicide applications are still the best way to reduce DON levels, additional strategies should be investigated to find ways to further reduce DON in grain.…”
Section: Discussionmentioning
confidence: 99%
“…Management strategies during harvest include wheat harvest at low moisture or A w , reduced mechanical seed damage, and the use of different grain harvest strategies to remove diseased kernels which are often lighter than the healthy ones. The use different harvesting configurations, with varying fan speeds and shutter openings, resulted in lower Fusarium-damaged wheat kernels and DON content in harvested wheat [99,100]. The removal of damaged grain implies a loss in the yield of harvested grain, but results in better storage conditions and improvement in grain safety offsetting the economic losses.…”
Section: Harvest and Postharvest Mitigation Measures And Managementmentioning
confidence: 99%